2024
DOI: 10.2142/biophysico.bppb-v21.s018
|View full text |Cite
|
Sign up to set email alerts
|

Application of single-molecule analysis to singularity phenomenon of cells

Michio Hiroshima,
Hiroko Bannai,
Gen Matsumoto
et al.

Abstract: Single-molecule imaging in living cells is an effective tool for elucidating the mechanisms of cellular phenomena at the molecular level. However, the analysis was not designed for throughput and requires high expertise, preventing it from reaching large scale, which is necessary when searching for rare cells that induce singularity phenomena. To overcome this limitation, we have automated the imaging procedures by combining our own focusing device, artificial intelligence, and robotics. The apparatus, called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…OptoTau is a protein fused to CRY2Olig [21], which forms multimeric complexes when exposed to blue light, with human 2N4R tau carrying the P301L mutation (Figure 1A). We have previously revealed that transient overexpression of OptoTau into Neuro2a and blue light exposure induced tau clustering [25] [26]. This study established Neuro2a cells that stably express OptoTau and investigated the effects of blue light illumination over a longer period than in previous studies.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…OptoTau is a protein fused to CRY2Olig [21], which forms multimeric complexes when exposed to blue light, with human 2N4R tau carrying the P301L mutation (Figure 1A). We have previously revealed that transient overexpression of OptoTau into Neuro2a and blue light exposure induced tau clustering [25] [26]. This study established Neuro2a cells that stably express OptoTau and investigated the effects of blue light illumination over a longer period than in previous studies.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, a series of studies revealed that transient overexpression of chimeric proteins combining tau with Cry2 or its derivative CRY2Olig, i.e., families of OptoTau, results in the blue light-dependent formation of LLPS droplets and tau oligomers [23] [24] [25] [26]. The present study manipulated tau by blue light in OptoTauKI cells, in which OptoTau was inserted into the genome by genome editing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations